ANALISIS PENYERAPAN TENAGA KERJA DI SEKTOR PARIWISATA KABUPATEN BLITAR STUDI KASUS PERIODE PANDEMI COVID-19 - Palupi, Endah Rekno; Bintoro, Nugroho Suryo (Journal of Development Economic and Social Studies, 2022)
As one of the sectors affected by the Covid-19 pandemic, the tourism sector in Blitar Regency experienced a large number of workers being absorbed in the tourism sector because the government issued a policy regarding the temporary closure of all tourism locations because it was considered to cause crowds that could increase the risk of the spread of Covid-19. This study uses a quantitative approach with the Partial Least Square (PLS) method through SmartPLS 3.0 software. The results of this study indicate that the wage variable has no significant effect on employment in the tourism sector in Blitar Regency during the Covid-19 pandemic, while the tourist variable and education level have a significant and negative effect on employment in the tourism sector in Blitar Regency during the Covid-19 pandemic. . In this study, it was found that during the Covid-19 pandemic, there was no absorption of labor in the tourism sector of Blitar Regency.